2019
DOI: 10.1063/1.5093978
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport in molecular beam epitaxy grown Si1 − xGex alloy films with a full spectrum of composition (x = 0–1)

Abstract: The thermal properties of Si1 – xGex alloys are important for two major reasons: one is their applications in high-temperature thermoelectrics and the other is the increasing heat dissipation demand for high power density devices. However, the large lattice mismatch between silicon and germanium leads to tremendous difficulties to obtain high-quality Si1 – xGex thin films, especially when x > 0.5. In this study, we obtained a series of high crystalline quality Si1 – xGex thin films with x covering all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Many experimental studies have been performed on the thermal conductivity of Si 1– x Ge x nanostructures. In general, the thermal conductivity changes significantly with the Ge concentration ( x ) when x is low (<0.2) or high (>0.8) but only varies marginally for 0.2 < x < 0.8. As to the size effect, it has been shown that boundary scattering could significantly suppress the thermal conductivity of SiGe thin films or nanowires, , confirming the prediction that phonons with MFPs below 1 μm contribute to less than 50% of the total thermal conductivity of bulk SiGe alloys. , However, the size dependence data tend to be scattered and are not able to support the superdiffusive thermal transport behavior.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Many experimental studies have been performed on the thermal conductivity of Si 1– x Ge x nanostructures. In general, the thermal conductivity changes significantly with the Ge concentration ( x ) when x is low (<0.2) or high (>0.8) but only varies marginally for 0.2 < x < 0.8. As to the size effect, it has been shown that boundary scattering could significantly suppress the thermal conductivity of SiGe thin films or nanowires, , confirming the prediction that phonons with MFPs below 1 μm contribute to less than 50% of the total thermal conductivity of bulk SiGe alloys. , However, the size dependence data tend to be scattered and are not able to support the superdiffusive thermal transport behavior.…”
mentioning
confidence: 80%
“…A series of Si 0.4 Ge 0.6 films were epitaxially grown on Si (100) substrates by using molecular beam epitaxy (MBE) (Section I, Supporting Information). 20 A reference sample without the Si 0.4 Ge 0.6 film was prepared through a similar process. Figure 1a shows a cross-sectional high-resolution transmission electron microscopy (HRTEM) image of the Si 0.4 Ge 0.6 film on Si substrate, indicating that the Si 0.4 Ge 0.6 /Si interface is clear and abrupt.…”
mentioning
confidence: 99%